2022
DOI: 10.1097/md.0000000000029034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of additional facet joint block for analgesia in patients with thoracolumbar compression fracture undergoing percutaneous kyphoplasty surgery

Abstract: Background: There is currently no pooled data in the literature to support whether additional facet joint block results in better clinical analgesia after percutaneous kyphoplasty. We assessed the existing evidence on the safety and efficacy of facet joint block in the treatment of patients with thoracolumbar compression fractures undergoing percutaneous kyphoplasty based on qualified trials.Methods: We will search PubMed, Springer, ScienceDirect, Wanfang, and Cochrane Library databases through April, 2022. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Therefore, the analysis of the risk factors of recurrent fracture after PKP is helpful to reduce the incidence of postoperative recurrent fracture. In our study, age, the number of operative vertebrae, BMD, the number of injured vertebrae, and the history of fracture were the risk factors of new fracture, which was consistent with most of the previous research results (27)(28)(29). With the increase of the age of patients, the probability of postoperative refracture increases remarkably, and it is considered that age is an independent risk factor for re-fracture after PKP (28).…”
Section: Logistic Regression Analysis Of Related Risk Factorssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the analysis of the risk factors of recurrent fracture after PKP is helpful to reduce the incidence of postoperative recurrent fracture. In our study, age, the number of operative vertebrae, BMD, the number of injured vertebrae, and the history of fracture were the risk factors of new fracture, which was consistent with most of the previous research results (27)(28)(29). With the increase of the age of patients, the probability of postoperative refracture increases remarkably, and it is considered that age is an independent risk factor for re-fracture after PKP (28).…”
Section: Logistic Regression Analysis Of Related Risk Factorssupporting
confidence: 93%
“…In our study, age, the number of operative vertebrae, BMD, the number of injured vertebrae, and the history of fracture were the risk factors of new fracture, which was consistent with most of the previous research results ( 27 - 29 ). With the increase of the age of patients, the probability of postoperative re-fracture increases remarkably, and it is considered that age is an independent risk factor for re-fracture after PKP ( 28 ). It was found that the proportion of age >75 years in the re-fracture group after PKP was 1.45 times higher than that of the non-fracture group.…”
Section: Discussionmentioning
confidence: 99%